Psychological and didactic problems of introducing a digital textbook into the educational process of a university - Lyudmila Valerievna Shelekhova; Sultanovna Fatimet Brantova (Вестник Майкопского государственного технологического университета)
The modernization of the higher education system, due to the rapid growth of digital technologies, implies a rethinking of the didactic and technological principles of organizing the educational process, creation and implementation of unique educational content, including electronic publications. Among the variety of electronic publications, a special place is occupied by a digital textbook. Despite the fact that the digital textbook is considered as the most promising means of organizing students' independent work in an electronic educational environment in the scientific and methodological literature. Today the influence of this tool on the of students and the organization of the educational process remains poorly understood. Before talking about the widespread introduction of a digital textbook, like any other innovative teaching tool, it is necessary to identify its impact on the psychophysiological characteristics of a student's personality. As a result, we can talk about the existence of a scientific problem: what impact should a digital textbook have on the subjects of the educational environment so that it can be considered as an integral structural component of the digital educational environment. The purpose of the research is to determine the potential of a digital textbook as an effective means of preparing a student for future professional activities, and to identify psychological and didactic problems that may be caused by the introduction of this innovative learning tool. The research methods used are analysis, questioning, conversation, survey, generalization, description, testing, Pearson's statistical test. The results of the research are the difference between a digital textbook and an electronic textbook and an electronic form of a textbook has been revealed. On the basis of the analysis of scientific and methodological literature and the results of empirical research, two main psychological and didactic problems of introducing a digital textbook into the educational process of a university have been identified: 1) it is associated with the consequence of an increase in the degree of direct impact on the mental processes of users of a digital textbook in the course of mastering or fixing educational material by them ; 2) due to the technical features of creating a digital textbook that meets the requirements of teaching aids; the experience of using the digital textbook "Mathematics for Economists" in the educational process in the direction of preparation 38.05.01 and 38.03.02 has been presented; the results of an online survey, a survey, a conversation between students and teachers about the advisability of using a digital textbook in the educational process have been shown. Key findings: online survey, conversation and survey of students has made it possible to identify students' interest in using a digital textbook in the educational process; analysis of web metrics of sections of the digital textbook contributed to determining the degree of its demand among students and university teachers; based on the results of testing students, at a significance level of 0.05 in accordance with the decision rule of the Pearson statistical criterion, the influence ofa digital textbook on the formation of educational results and on the speed of mastering educational material was revealed. Based on the results of a survey of students and conversations with teachers, the following ways have been identified: 1) improving the digital textbook as a learning tool, taking into account its impact on the psychophysiological characteristics of a student's personality; 2) optimization of the educational process, taking into account the use of a digital textbook.